The Monetary Theory of Deficit Spending - Warburton, Clark (The Review of Economics and Statistics, 1945)
THE effect of fiscal operations of government, particularly of the federal government, upon the national income stream has been the focal point of a large part of economic theory in recent years. This emphasis has been expressed in three forms: (i) logical analyses, frequently using the symbolism of mathematics, of relationships between government expenditures -particularly expenditures in excess of taxation or in excess of cash receipts other than borrowing and business fluctuations; (2) factual statistical analyses of relationships between government expenditures in excess of taxation or of cash receipts on the one hand, to the amount of the national income, or some other measure of the income stream, on the other; and (3) proposals for governmental policy of two general types (a) rearrangement and simplification of the federal government budget to show the above relationships, and (b) the pursuit, intermittently or permanently, of a policy of government spending in excess of government revenue.1 That the effect of government fiscal operations upon income flow, particularly the effect of a policy of deficit spending, is associated with monetary phenomena has been recognized by most of the economists who place great hopes on budgetary management as a device for promoting economic stability at a high rate of employment and production.2 However, the theory of this type of fiscal management has not been well integrated with the general body of monetary theory. That relationship to monetary theory is the subject of this article.